2020
DOI: 10.1073/pnas.2007232117
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis between nanohaloarchaeon and haloarchaeon is based on utilization of different polysaccharides

Abstract: Nano-sized archaeota, with their small genomes and limited metabolic capabilities, are known to associate with other microbes, thereby compensating for their own auxotrophies. These diminutive and yet ubiquitous organisms thrive in hypersaline habitats that they share with haloarchaea. Here, we reveal the genetic and physiological nature of a nanohaloarchaeon–haloarchaeon association, with both microbes obtained from a solar saltern and reproducibly cultivated together in vitro. The nanohaloarchaeon Candidatus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
114
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 55 publications
5
114
2
Order By: Relevance
“…LC1Hm (Fig. 2) seems to be mutualistic, at least under some conditions, and based on different polysaccharide‐metabolizing activities (La Cono et al ., 2020). The haloarchaeon usually degrades chitin extracellularly, producing beta‐glucans that it consumes.…”
Section: Expanding Prokaryote – Prokaryote Symbioses: Cpr and Dpann Pmentioning
confidence: 99%
See 2 more Smart Citations
“…LC1Hm (Fig. 2) seems to be mutualistic, at least under some conditions, and based on different polysaccharide‐metabolizing activities (La Cono et al ., 2020). The haloarchaeon usually degrades chitin extracellularly, producing beta‐glucans that it consumes.…”
Section: Expanding Prokaryote – Prokaryote Symbioses: Cpr and Dpann Pmentioning
confidence: 99%
“…Nanohalobium ferments glycogen or starch (alpha‐glucans that the host does not metabolize), making their products accessible to the host which, in turn, sustains its metabolically limited epibiont. Nonetheless, whether this strategy maximizes the long‐term fitness of the host (La Cono et al ., 2020) or whether Ca . Nanohalobium becomes parasitic in the presence of chitin and/or in the absence of glycogen or starch in the environment remains to be established.…”
Section: Expanding Prokaryote – Prokaryote Symbioses: Cpr and Dpann Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them, notably CPR bacteria, are parasites/predators 26,27 ; others can display mutualistic interactions (e.g. complementation of host’s metabolism to degrade specific substrates 28 ) although, upon environmental change, they likely behave as parasites, shifting along the mutualism-parasitism continuum 29 . Testing these hypotheses ultimately requires reliable quantification of virus-to-cell and episymbiont versus free-living cell ratios that can be comparatively applied across biomes.…”
mentioning
confidence: 99%
“…Very recently, culture-dependent and -independent researches revealed that Ca. Nanohaloarchaeota had the capability of poly-or oligo-saccharide degradation in hypersaline brines of saltern and soda lakes [12,21]. Besides, the methylotrophic methanogenesis was evidently a dominant process, and many haloalkaliphilic methylotrophic methanogens were isolated from soda lakes, including Methanolobus, Methanosalsum, Methanocalculus and Methanonatronarchaeum [22,23].…”
mentioning
confidence: 99%